Smooth trajectory tracking interpolation on a robot simulator - Pacheco R.R.* (2010)
When there is the need of a robotic manipulator to follow a certain smooth and continuous trajectory, it involves the specification of the curve to be followed and the way the gripper should behave alongside it. This work aims to identify and analyze a technique to be used in a 3D virtual robotic simulator that executes smooth and continuous movements. It also aims to develop a method for trajectory programming using a solution that covers the main problems of trajectory tracking (smoothness of path and gripper approach). An efficient and flexible method to embed trajectory tracking was indentified and implemented which allows its integration with existing standard (linear or circular) movements. © 2010 IEEE.